Representasi Kecemasan dan Ketakutan dalam Sastra Realisme Psikologis: Analisis Psikologi Tokoh dalam Cerpen Apa yang Lebih Kuat dari Maut karya Mashdar Zainal - Sari, Dewi Masitoh Arum (Maliki Interdisciplinary Journal, 2024)
This study analyzes the short story Apa yang Lebih Kuat dari Maut by Mashdar Zainal through a psychological realism approach, while integrating Freudian and Jungian perspectives to explore the forms of anxiety and fear experienced by the main character. The story depicts a deep internal conflict, where the fear of death and social pressure are key elements shaping the character's psychology. From a Freudian perspective, this fear can be seen as a result of the tension between destructive instinctual drives (id), societal values (superego), and the will to survive (ego). Meanwhile, from a Jungian perspective, this anxiety serves as part of the individuation process, where the protagonist confronts the shadow, the neglected dark side of their personality. Through narrative analysis, this study demonstrates how existential anxiety and fear of death shape the character’s actions and decisions, as they become trapped in a dilemma between the desire for a meaningful life and social rejection of a love deemed taboo. This research contributes to enriching the understanding of the role of fear in psychological literature and opens avenues for further study on the influence of social norms and love in shaping an individual's inner dynamics.